Propagation of surface plasmons on plasmonic Bragg gratings - Chaves, A. J. (2019)
We use coupled-mode theory to describe the scattering of a surface-plasmon polariton (SPP) from a square wave grating (Bragg grating) of finite extension written on the surface of either a metal-dielectric interface or a dielectric-dielectric interface covered with a patterned graphene sheet. We find analytical solutions for the reflectance and transmittance of SPP's when only two modes (forward- and back-scattered) are considered. We show that in both cases the reflectance spectrum presents stop-bands where the SPP is completely back-scattered, if the grating is not too shallow. In addition, the reflectance coefficient shows Fabry-P\'erot oscillations when the frequency of the SPP is out of the stop-band region. For a single dielectric well, we show that there are frequencies of transmission equal to 1. We also provide simple analytical expression for the different quantities in the electrostatic limit.